ЗАМОНАВИЙ ТИЛШУНОСЛИКНИНГ БАЪЗИ МАСАЛАЛАРИГА ДОИР (Scientific journal of the Fergana State University, 2023)
The article considers the issue of terminology and the place of pragmalinguistics among the structure of linguistic spheres.